1974
DOI: 10.1099/00221287-83-1-51
|View full text |Cite
|
Sign up to set email alerts
|

Events Surrounding the Early Development of Euglena Chloroplasts: Experiments with Streptomycin in Non-dividing Cells

Abstract: The concentration of streptomycin (Sm) which selectively inhibits light-induced chloroplast development in non-dividing Euglena is the same as that which induces the loss of green-colony forming ability in dividing organisms. This concentration of Sm has no effect on division or viability. Chlorophyll synthesis is insensitive to streptomycin for the first 1 2 h of development but is strongly inhibited after this time. Between 72 and 96 h after the beginning of chloroplast development, Sm-treated organisms cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 19 publications
5
17
0
Order By: Relevance
“…In this case cycloheximide blocks the formation of Chl and Cyt-552 almost completely while streptomycin inhibits both Chl and Cyt-552 by only 40%o after 8 h, the time for complete permeation. These observations are in agreement with others (4,8,11) indicating that antibiotics which affect chloroplast translation have less effect when they are added later during chloroplast development. Although no satisfactory explanation has been advanced for this phenomenon, the fact that Cyt-552 and Chl behave in the same manner once again suggests that the factors affecting their synthesis are very similar.…”
Section: Resultssupporting
confidence: 82%
“…In this case cycloheximide blocks the formation of Chl and Cyt-552 almost completely while streptomycin inhibits both Chl and Cyt-552 by only 40%o after 8 h, the time for complete permeation. These observations are in agreement with others (4,8,11) indicating that antibiotics which affect chloroplast translation have less effect when they are added later during chloroplast development. Although no satisfactory explanation has been advanced for this phenomenon, the fact that Cyt-552 and Chl behave in the same manner once again suggests that the factors affecting their synthesis are very similar.…”
Section: Resultssupporting
confidence: 82%
“…This concentration of chloramphenicol has little effect on cell division or viability in Euglena, suggesting that it does not block protein synthesis on cytoplasmic ribosomes. This ineffectiveness has been confirmed by Bovarnick et al (4,5) who reported that chloramphenicol, even at 2 mg/ml, did not prevent the synthesis of NADP-linked triose phosphate dehydrogenase in regreening Euglena. This enzyme is apparently translated on 87S cytoplasmic ribosomes since its synthesis was completely prevented by 15 ,ug/ml of cycloheximide (5).…”
Section: Resultssupporting
confidence: 58%
“…The activity of this enzyme increases, along with the cellular level of chlorophyll and other enzymic and structural components of the developing chloroplast, for 3 to 4 days, by which time the cells are fully regreened and photosynthetically competent (4,7). In a previous publication, we reported that if at anytime during the regreening process the cells are transferred back into darkness, there is a striking continued synthesis of RuDPCase in the dark (21).…”
mentioning
confidence: 99%
“…The activity of this enzyme increases along with other enzymic and structural components of the developing chloroplast, for 3 to 4 days, by which time the cells are photosynthetically competent (4,7). If at any time during the regreening process Euglena cells are transferred back into darkness there is a striking continued synthesis of RuDP Case in the dark (10,11).…”
mentioning
confidence: 99%